(untitled) (Research, Society and Development, 2022)
Objective: This study aims to compare the effects of age at first sexual intercourse (sexarche) and menarche-sexarche interval in predicting the incidence of human papillomavirus (HPV)-induced lesions. Material & Methods: This is a cross-sectional study of 698 women with normal or HPV-induced lesions, diagnosed cytologically or histologically. Results: After multivariate analysis, the probability of developing HPV-induced lesions increased by 63% for those with menarche-sexarche interval of 3 years or less. Additionally, smoking, parity, and age were relevant in prediciting the risk. Conclusion: Sexarche within the first 3 years from menarche was associated with the occurrence of HPV-induced lesions as an independent factor, unlike sexarche, indicating that menarche-sexarche interval of less than 3 years may be an important parameter for the definition of early sexual intercourse.